2018
DOI: 10.5513/jcea01/19.1.2032
|View full text |Cite
|
Sign up to set email alerts
|

The influence of stages of maturity on the agronomic traits of fibre flax introduced varieties

Abstract: The harvest time of fibre flax is influenced by climatic conditions, varieties, stages of maturity and the crop's final use. In addition, the time of harvesting of fibre flax affects the quality of the fibres. Fibre flax can be harvested in few stages of maturity. So, this paper presents the influence of three stages of maturity (green, yellow and full ripening) on the agronomic traits (stem yield, stem yield after retting, total fibre yield, share of total fibre, long fibre yield, share of long fibre) of five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Fibre flax have the main yield fibre, whereas linseed (oilseed flax) have seeds as the primary yield and straw is the secondary yield. As morphological differences, the fibre flax is 80-150 cm tall and poorly branched, while linseed is 45-80 cm tall and more branched (Couture et al, 2002;Pospišil, 2013;Butorac et al, 2017;Butorac et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Fibre flax have the main yield fibre, whereas linseed (oilseed flax) have seeds as the primary yield and straw is the secondary yield. As morphological differences, the fibre flax is 80-150 cm tall and poorly branched, while linseed is 45-80 cm tall and more branched (Couture et al, 2002;Pospišil, 2013;Butorac et al, 2017;Butorac et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For more than 20 years, there has been cooperation between agronomists and textile-oriented specialists with the aim of revitalizing the sustainable and ecological production of flax fibres in Croatia. Since Croatia does not have its own cultivars [ 5 , 6 ], it is necessary to introduce cultivars from Europe, which are grown in climatic conditions similar to Croatian cultivars [ 7 , 8 , 9 , 10 , 11 , 12 ]. Therefore, it may be assumed that the newly formed climate conditions would cause the reduction in the valuable properties of flax plant and fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the obtained results, the investigation continued, and the influence of nitrogen fertilization on the agronomic properties (dry stem yield, dry stem yield after retting, total fibre yield, share of total fibre, long fibre yield and share of long fibre) of fibre flax cultivars was investigated [ 11 ]. Based on the analysis of the results, it was concluded that the cultivars, Agatha, Viola and Electra, recorded the highest values for the investigated properties (dry stem yield, dry stem yield after retting, total fibre yield, long fibre yield) over three years and the highest share of total fibres and long fibres over one or two years.…”
Section: Introductionmentioning
confidence: 99%